Task-Level Authoring for Remote Robot Teleoperation - Senft, Emmanuel; Hagenow, Michael; Welsh, Kevin; Radwin, Robert; Zinn, Michael; Gleicher, Michael; Mutlu, Bilge (Frontiers in Robotics and AI, 2021)
Remote teleoperation of robots can broaden the reach of domain specialists across a wide range of industries such as home maintenance, health care, light manufacturing, and construction. However, current direct control methods are impractical, and existing tools for programming robot remotely have focused on users with significant robotic experience. Extending robot remote programming to end users, i.e., users who are experts in a domain but novices in robotics, requires tools that balance the rich features necessary for complex teleoperation tasks with ease of use. The primary challenge to usability is that novice users are unable to specify complete and robust task plans to allow a robot to perform duties autonomously, particularly in highly variable environments. Our solution is to allow operators to specify shorter sequences of high-level commands, which we call task-level authoring, to create periods of robot autonomy. This approach allows inexperienced users to create robot behaviors in uncertain environments by interleaving exploration, specification of behaviors, and execution as separate steps. End-users are able to break down the specification of tasks and adapt to the current needs of the interaction and environments. In this paper, we describe a prototype system contextualized in light manufacturing and its empirical validation in a user study with 18 participants. Participants were able to perform a variety of complex telemanipulation tasks with little training. Our results show that our approach allowed users to create periods of autonomy and solve rich manipulation tasks. Furthermore, participants significantly preferred our system over comparative more direct interfaces, demonstrating the potential of our approach for enabling novice users to effectively perform remote robot programming.